Food insecurity (hunger) and fast-food consumption among 180 164 adolescents aged 12–15 years from sixty-eight countries. Issue 3 (14th February 2022) - Smith, Lee; Barnett, Yvonne; López-Sánchez, Guillermo F.; Shin, Jae Il; Jacob, Louis; Butler, Laurie; Cao, Chao; Yang, Lin; Schuch, Felipe; Tully, Mark; Koyanagi, Ai
Abstract: Food insecurity has been shown to be associated with fast-food consumption. However, to date, studies on this specific topic are scarce. Therefore, the aim of the present study was to investigate the association between food insecurity and fast-food consumption in adolescents aged 12–15 years from sixty-eight countries (seven low-income, twenty-seven lower middle-income, twenty upper middle-income, fourteen high-income countries). Cross-sectional, school-based data from the Global School-based Student Health Survey were analysed. Data on past 30-d food insecurity (hunger) and fast-food consumption in the past 7 d were collected. Multivariable logistic regression and meta-analysis were conducted to assess associations. Models were adjusted for age, sex and BMI. There were 180 164 adolescents aged 12–15 years (mean age 13·8 (sd 1·0) years; 50·8 % boys) included in the analysis. Overall, severe food insecurity (i.e. hungry because there was not enough food in home most of the time or always) was associated with 1·17 (95 % CI 1·08, 1·26) times higher odds for fast-food consumption. The estimates pooled by country-income levels were significant in low-income countries (adjusted OR (aOR) = 1·30; 95 % CI 1·05, 1·60), lower middle-income countries (aOR = 1·15; 95 % CI 1·02, 1·29) and upper middle-income countries (aOR = 1·26; 95 % CI 1·07, 1·49), but not in high-income countries (aOR = 1·04; 95 % CI 0·88, 1·23). The mere co-occurrence of food insecurity and fast-food consumption is of public health importance. To tackle this issue, a strong governmental and societal approach is required to utilise effective methods as demonstrated in some high-income countries such as the implementation of food banks and the adoption of free school meals.